Fossil Chondrichthyes from the Neogene of Portugal: Diversity and Occurrence - Fialho, Pedro (2022)
Portugal has a rich fossil record both on the continent and in the Azores islands (Santa Maria). For decades, researchers have found thousands of fossils and identified hundreds of species from major taxonomic groups. The present work focuses on analyzing the scientific literature on fossils of Chondrichthyes collected in fossiliferous deposits of the Neogene. Fossils of sharks and rays, teeth,dermal denticles, and caudal spines were discovered in deposits from Aquitanian to Piacenzian (Neogene). About 105 deposits were identified and studied on the mainland and on the Island of Santa Maria, most of which have disappeared or are currently inaccessible. In total, 36 publications list 91 species of Chondrichthyes, 11 of which were described for the first time in Portugal, and 61 genera. Twelve orders are represented in the material published so far.